Effect of biofertilizers on the vegetative growth and yield of oyster mushroom (Pleurotus spp.) - Thakur, M P; Ranjan, S; Shukla, C S; Gupta, S B (Mushroom Research, 2012)
Effect of biofertilizers on spawn run and yield of Pleurotus sapidus, P. florida, P. flabellatus and P. sajor-caju in different years was studied. It was found that none of the biofertilizers promoted the mycelial development and yield of P. sapidus compared to control. Significant difference in yield of P. florida was recorded with different biofertilizers in their different concentrations. The yield of P. florida was significantly high (107.0% BE) in Dehra EM at 0.4% concentration when mushroom beds were sprayed with biofertilizer. On the other hand, the yield of P. flabellatus was significantly high in Dehra EM at 0.6% (71% BE) and 0.2% concentrations (59% BE), while of P. florida in Dehra EM at 0.4% (120.33% BE) on immersion of mushroom beds were immersed in the solution of biofertilizers. Biofertilizer of different concentrations has no significant effect on number of sporophores obtained in P. sajor-caju. On the contrary, the yield of P. sajor-caju was significantly high in Dehra EM at 0.6% (97.30 BE), 0.4% (91% BE) and 0.2% concentrations (69% BE) whereas, it was less at Dehra EM 0.8% concentration.